The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12020187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music on Stress Parameters in Dogs during a Mock Veterinary Visit

Abstract: Veterinary visits can be stressful for dogs, but how their wellbeing changes during a visit is not well understood. Music therapy has been successfully used in clinical practice to alleviate stress and anxiety in people. The present study aimed to understand how canine stress changes during a veterinary visit, establish the effect of music, and highlight measures which may be of practical use. In a randomized crossover design, dogs were exposed to no music and a bespoke piece of classical music at a tempo desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
6
1
Order By: Relevance
“…In the current study surface temperatures of the nose and eye were significantly lower for the high arousal negative valence scenario compared to the high arousal positive valence scenario. This is contrary to previous findings, which have indicated that temperature increases in response to stress 39 , 96 , 113 , 136 . While testing and sampling areas were maintained at consistent temperatures throughout the study, dogs had to walk outside from the car to the sampling room prior to collection of the temperature readings.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the current study surface temperatures of the nose and eye were significantly lower for the high arousal negative valence scenario compared to the high arousal positive valence scenario. This is contrary to previous findings, which have indicated that temperature increases in response to stress 39 , 96 , 113 , 136 . While testing and sampling areas were maintained at consistent temperatures throughout the study, dogs had to walk outside from the car to the sampling room prior to collection of the temperature readings.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite this, numerous studies across a range of species and situations have demonstrated associations between QBA scores and physiological parameters, e.g. 38 , 39 , 120 122 . However, some studies have also failed to find an association 123 , 124 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All videos were scored by two trained raters on a series of behavior attributes using a QBA previously developed to evaluate the welfare of shelter dogs in a mock veterinary setting ( Arena et al., 2019 ; King et al., 2022 ). This QBA was modified to be more relevant to the test (car travel) used in this study, resulting in 17 terms: anxious, alert, calm, comfortable, depressed, explorative, fearful, lethargic, nauseous, nervous, reactive, relaxed, restless, sad, stressed, tense, and uncomfortable.…”
Section: Methodsmentioning
confidence: 99%